Identification of MET genomic amplification, protein expression and alternative splice isoforms in neuroblastomas. Issue 11 (25th June 2013) - Yan, Benedict; Lim, Malcolm; Zhou, Lihan; Kuick, Chik Hong; Leong, May Ying; Yong, Kol Jia; Aung, LeLe; Salto-Tellez, Manuel; Chang, Kenneth T E
Abstract : Background: Crizotinib, a dual anaplastic lymphoma kinase (ALK) and mesenchymal-epithelial transition (MET) tyrosine kinase inhibitor, is currently being evaluated for the treatment of neuroblastoma. Its effects are thought to be mediated mainly via its activity against ALK. Although MET genomic/protein expression status might conceivably affect crizotinib efficacy, this issue has hitherto not received attention in neuroblastomas. Aims/Methods: MET genomic and protein expression status was characterised by silver in situ hybridisation and immunohistochemistry (IHC) respectively, in a cohort of 54 neuroblastoma samples. MET splice isoforms were characterised in 15 of these samples by quantitative PCR. Results: One case (1/54; prevalence 1.85%) displayed MET genomic amplification, while another case (1/54; prevalence 1.85%) displayed strong membranous MET protein expression (IHC score 3+). Alternative exon 10-deleted and exon 14-deleted MET splice isoforms were identified. Conclusions: MET amplification and protein expression, although low in prevalence, are present in neuroblastomas. This has implications when crizotinib is employed as a therapeutic agent in neuroblastomas. Additionally, the existence of alternatively spliced MET isoforms may have clinical and biological implications in neuroblastomas.